Development and Optimization of Micro/Nanoporous Osmotic Pump Tablets - Tuntikulwattana, Siracha (Springer US, 2010)
Micro/nanoporous osmotic pump tablets coated with cellulose acetate containing polyvinylpyrolidone (PVP) as pore formers were fabricated. Propranolol hydrochloride was used as a model drug in this study. Formulation optimization based on USP 31 requirements was conducted following a central composite design using a two-level factorial plan involving two membrane variables (pore former and coating levels). Effect of molecular weight of pore former (PVP K30 and PVP K90) was also evaluated. Responses of drug release to the variables were analyzed using statistical software (MINITAB 14). Scanning electron microscopy and atomic force microscopy showed that the pores formed by PVP. The drug release was dependent on the molecular weight and concentration of PVP and the level of coating. The results showed that acceptable 12-h profile could be achieved with only specific range of PVP K30-containing membrane at the defined membrane thickness. However, satisfactory 24-h profile could be accomplished by both PVP K30 and PVP K90-containing membrane at the range and membrane thickness tested. Preparation and testing of the optimized formulation showed a good correlation between predicted and observed values.